2007
DOI: 10.1523/jneurosci.1800-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Agents Sensitize C-Type Nociceptors by Relieving High-Affinity Zinc Inhibition of T-Type Calcium Channels

Abstract: Recent studies have demonstrated an important role for T-type Ca2ϩ channels (T-channels) in controlling the excitability of peripheral pain-sensing neurons (nociceptors). However, the molecular mechanisms underlying the functions of T-channels in nociceptors are poorly understood. Here, we demonstrate that reducing agents as well as endogenous metal chelators sensitize C-type dorsal root ganglion nociceptors by chelating Zn 2ϩ ions off specific extracellular histidine residues on Ca v 3.2 T-channels, thus reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
164
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(190 citation statements)
references
References 51 publications
20
164
3
2
Order By: Relevance
“…The average IC 50 values for the Ca v 3.1 and Ca v 3.2 currents were 82.2 Ϯ 6.9 and 3.0 Ϯ 0.2 M, respectively (n ϭ 13, 42; open symbols in Fig. 1, E and F), being consistent with the previously reported findings performed in HEK-293 cells (14,17). The half-potentials for their activation and steady-state inactivation were not significantly changed by zinc ( (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The average IC 50 values for the Ca v 3.1 and Ca v 3.2 currents were 82.2 Ϯ 6.9 and 3.0 Ϯ 0.2 M, respectively (n ϭ 13, 42; open symbols in Fig. 1, E and F), being consistent with the previously reported findings performed in HEK-293 cells (14,17). The half-potentials for their activation and steady-state inactivation were not significantly changed by zinc ( (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We first confirmed the Xenopus oocyte expression system could be used to measure the higher potency of zinc to inhibit Ca v 3.2 over Ca v 3.1 channels, which was originally observed in mammalian cells (14,17). Application of serial zinc solutions demonstrated that Ca v 3.2 currents were sensitively inhibited by low micromolar concentrations of zinc, whereas Ca v 3.1 currents required much higher concentrations (Fig.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…16 Modulation of the Ca v 3.2 (α1H) channel controls the sensitization of nociceptors, the peripheral painsensing neurons. 17 These results further support Ca v 3.2 T-type channels as a mechanism for modulating nociceptive sensitivity.High throughput screening (HTS) generated a number of sulfonamide hits including 1 (IC 50 = 3 μM) and 2 (IC 50 = 5 μM) (Figure 1) against Ca v 3.2 T-type channel in a FLIPR based Ca 2+ flux assay. 18,19 However, HTS hits 1 and 2 are metabolically unstable in rats and both have very poor oral bioavailability (F = 0.5% and 1.9%, respectively) ( Table 1).…”
supporting
confidence: 53%
“…16 Modulation of the Ca v 3.2 (α1H) channel controls the sensitization of nociceptors, the peripheral painsensing neurons. 17 These results further support Ca v 3.2 T-type channels as a mechanism for modulating nociceptive sensitivity.…”
supporting
confidence: 53%